Impact of local elasticity and inner rotating circular cylinder on the magneto-hydrodynamics forced convection and entropy generation of nanofluid in a U-shaped vented cavity - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Sheikholeslami, Mohsen (Wiley, 2020)
This study analyzes the effects of a partial elastic wall and rotating circular cylinder on the convective heat transfer of carbon nanotube (CNT)-water nanofluid filled U-shaped cavity with entropy generation by considering inclined magnetic field effects. Numerical simulation is performed by using ALE with finite element method (FEM). Impacts of various important parameters such as Re number, Ha number, magnetic field orientation, elastic wall size and modulus, angular velocity, and horizontal position of the rotating cylinder on the forced convection are analyzed. When the values of Re number, strength of magnetic field (up to Ha number of 50), and orientation angle are increased, the average Nu value rises while the impact is opposite for higher elastic wall size and horizontal position of the cylinder above 0.4H. When the rotational cylinder effects are considered, enhancement up to 60%is obtained at the highest speed as compared to motionless cylinder case. The average Nu variation is in the range of 9%-10.45%at the highest value when varying the size and modulus of the elastic wall. Flexible wall effects on the average Nu number variation becomes more pronounced when the angular rotational velocity is highest at the clockwise rotation and for the highest Re number. The average Nu number enhancements are 13%-14%at the highest Ha number. The entropy generation rates with varying Ha number, rotational velocity, and location of the cylinder are different for the left and right parts of the domains while impacts of elastic wall properties on the entropy generation rate are slight.
Keywords: entropy generation; finite element method; local elastic wall; MHD; rotating cylinder; U-shaped cavity